Moving towards a new growth model: Policy options - Michael Böheim; Anna Strauss; Teresa Weiss (WWWforEurope, 2015)
The report summarized the main contents that were presented at the Second WWWforEurope Feedback Conference, taking place on May 6th 2015 in Vienna. After 38 months of extensive work on essential questions for Europe's future with a particular focus on laying the analytical basis for a socio-ecological transition the conference marked the end of the second phase, the policy formulation phase, of the project, as well as the beginning of the third phase, the synthesis phase. Moreover, it was dedicated to collect impulses for the project's synthesis report, which represents the main output at the end of the project. For this purpose, external experts and stakeholder representatives from European/international institutions, social partners, NGOs and academia joined the conference and had the possibility to directly give feedback to outputs of the project. A collection of written statements provided by the stakeholders reflect how different research groups, partners and stakeholders approach the core issues of the project. Beside contributions of Karl Aiginger (project coordinator) and Catherine Mann (OECD), the report further includes five Area Chapters representing the results of the work of the five WWWforEurope Research Areas.
Keywords: 330; Wirtschaftswachstum; Wirtschaftsmodell; EU-Staaten